THE USE OF KWL STRATEGY COMBINED WITH PICTURE TO IMPROVE READING COMPREHENSION OF THE EIGHTH GRADE STUDENTS OF SMP N 2 TAMPAKSIRING IN ACADEMIC YEAR 2020/2021 - Dewa Gede Juli Astika; I Gusti Agung Putri Wirastuti (Academic Journal on English Studies (AJOES), 2021)
Reading comprehension is a crucial skill needs to be developed because the readers needto comprehend their readings in order to obtain the useful information. This study was aimedto find out whether or not the subjects’ reading comprehension can be improved throughKWL strategy combined with picture. The subjects were the eighth grade students of SMP N2 Tampaksiring in academic year 2020/2021. Based on the result of pre-test, it was foundthat many students had problems in identifying general and specific information, textualmeaning and textual reference. Therefore, the KWL strategy combined with picture wascarried out which divided into two cycles. The data were gathered by administering post-test1 and post-test 2 in the end of each cycle. The mean scores of pre-test, post test 1, and posttest2 were respectively, 52.03, 66.17, and 76.17. The result of the post-tests showed thesignificant improvements toward subjects’ reading comprehension. Moreover, the result ofquestionnaire showed that the subjects positively responded toward the use of KWL Strategycombined with picture. In conclusion, this study proved that reading comprehension of theeighth grade students of SMP N 2 Tampaksiring in academic year 2020/2021 could beimproved by using KWL Strategy combined with picture.